PENGARUH KOMPETENSI SUMBERDAYA APARATURT ERHADAP EFEKTIVITAS PENYELENGGARAAN ADMINISTRASI PERKANTORAN DI DINAS KESEHATAN KABUPATENMINAHASA UTARA - Mandagi, Wicke; Pangkey, Masje Silija; Dengo, Salmin (Sam Ratulangi University, 2016)
ABSTRAK :Human resources is an important factor determining the effectiveness of the organization. The purpose of this study was to determine / measure the extent of the influence of competence sumnberdaya apparatus of the effectiveness of the administration offices in North Minahasa Regency Health Office.This study uses quantitative methods. The respondents are all employees / officials at Health Office of North Minahasa Regency as many as 40 people. Instruments and data collection techniques used are questionnaires and aided by structured interview (interview quide). The analysis technique used to test the hypothesis is simple statistical regression analysis and simple correlation or koreasi product moment.The result showed: (1) the coefficient of regression toward the competence of personnel resources on the effectiveness of the administration office is posifive and significant. (2) The correlation coefficient and coefficient of determination variable competence of personnel resources on the effectiveness of the administration of the office is significant.Based on the results of these studies conclude that the competence of personnel resources have a relationship and a positive and significant impact on the effectiveness of the administration offices.Departing from the conclusions suggested let the competence development of personnel resources as a tool or a means to improve the effectiveness of the administration offices.Keywords : Competency Resource Apparatus , Office Administration